PAI-1 Regulates the Invasive Phenotype in Human Cutaneous Squamous Cell Carcinoma. (31st December 2009) - Freytag, Jennifer; Wilkins-Port, Cynthia E.; Higgins, Craig E.; Carlson, J. Andrew; Noel, Agnes; Foidart, Jean-Michel; Higgins, Stephen P.; Samarakoon, Rohan; Higgins, Paul J.
Abstract : The emergence of highly aggressive subtypes of human cutaneous squamous cell carcinoma (SCC) often reflects increased autocrine/paracrine TGF-β synthesis and epidermal growth factor receptor (EGFR) amplification. Cooperative TGF-β /EGFR signaling promotes cell migration and induces expression of both proteases and protease inhibitors that regulate stromal remodeling resulting in the acquisition of an invasive phenotype. In one physiologically relevant model of human cutaneous SCC progression, TGF-β 1+EGF stimulation increases the production of several matrix metalloproteinases (MMPs), among the most prominent of which is MMP-10—an MMP known to be elevated in SCC in situ. Activation of stromal plasminogen appears to be critical in triggering downstream MMP activity. Paradoxically, PAI-1, the major physiological inhibitor of plasmin generation, is also upregulated under these conditions and is an early event in progression of incipient epidermal SCC. One testable hypothesis proposes that TGF-β 1+EGF-dependent MMP-10 elevation directs focalized matrix remodeling events that promote epithelial cell plasticity and tissue invasion. Increased PAI-1 expression serves to temporally and spatially modulate plasmin-initiated pericellular proteolysis, further facilitating epithelial invasive potential. Defining the complex signaling and transcriptional mechanisms that maintain this delicate balance is critical to developing targeted therapeutics for the treatment of human cutaneous malignancies.